Cool East Coast cooking : easy and fun regional recipes - Kuskowski, Alex. (Minneapolis, Minn. : ABDO Pub. Co., 2014)
Simple text and photographs present recipes from the eastern region of the United States.
Discover East Coast Eats -- Learn about the East Coast -- The Basics -- Cool Cooking Terms -- The Tool Box -- The Ingredients -- Johnnycake Breakfast -- Creamy Clam Chowder -- Maine Pumpkin Bread -- Fry-It-Up Fish 'n' Chips -- Three Sisters Soup -- Philly Cheesesteak Sandwich -- Big Apple Cheesecake -- Classy Molasses Cookies -- Conclusion -- Glossary -- Web Sites.
Includes index.
4.8
3-6
Keywords: Cooking, American -- Juvenile literature; Cooking -- East (U.S.) -- Juvenile literature; Cooking -- Atlantic Coast (U.S.) -- Juvenile literature; Cooking, American; Cooking -- East (U.S.); Cooking -- Atlantic Coast (U.S.); American cooking; Cooking -- East (U.S.); Cooking -- Atlantic Coast (U.S.); Cookbooks; Cooking, American; Cookbooks; Cookbooks